(untitled) (Homoeopathy for All, 2021)
When stomach flu hits, it hits hard. It’s usually caused by a virus, but it’s not the flu virus, so it’s not actually stomach flu. Bacteria and parasites also can cause it. Gastroenteritis is a short-term illness triggered by the infection and inflammation of the digestive system. Symptoms can include abdominal cramps, diarrhoea and vomiting. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.